2010
DOI: 10.1038/nmat2745
|View full text |Cite
|
Sign up to set email alerts
|

Dissolvable films of silk fibroin for ultrathin conformal bio-integrated electronics

Abstract: Electronics that are capable of intimate, non-invasive integration with the soft, curvilinear surfaces of biological tissues offer important opportunities for diagnosing and treating disease and for improving brain-machine interfaces. This paper describes a material strategy for a type of biointerfaced system that relies on ultrathin electronics supported by bioresorbable substrates of silk fibroin. Mounting such devices on tissue and then allowing the silk to dissolve and resorb initiates a spontaneous, confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1,379
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,511 publications
(1,417 citation statements)
references
References 30 publications
4
1,379
0
6
Order By: Relevance
“…As shown in Figure 3 a, the conformal contact issue of neural electrode array can be simplified as how to keep a membrane wrapping around a cylinder with certain radius. The formula of the conformal critical diameter is shown as the following5 γγnormalc=EIR2bwhere γ is the adhesion energy per unit area, b is the width of PI pad ( b = 3690 µm, Figure S7, Supporting Information). γ is about 10 mJ m −2 , according to the reported values for wet interfaces 5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 3 a, the conformal contact issue of neural electrode array can be simplified as how to keep a membrane wrapping around a cylinder with certain radius. The formula of the conformal critical diameter is shown as the following5 γγnormalc=EIR2bwhere γ is the adhesion energy per unit area, b is the width of PI pad ( b = 3690 µm, Figure S7, Supporting Information). γ is about 10 mJ m −2 , according to the reported values for wet interfaces 5.…”
Section: Resultsmentioning
confidence: 99%
“…As the core of neurophysiologic monitoring, realizing high‐quality signal collection is an important topic in the research of neural electrode arrays. Related researches have indicated that stretchable/flexible neural electrode arrays, with their excellent mechanical and electrical performance, are superior candidates for the next generation of implantable devices 3, 4, 5, 6, 7, 8, 9, 10, 11. The successful development of stretchable/flexible neural electrode arrays hinges on good conformal contact between the array and the tissue, which enables excellent mechanical and electrical properties,3 as well as low‐cost, stable, and high‐throughput manufactural techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stretchable electronic devices have great advances for implantable devices in the human body 164, 165, 166. Stretchable devices, such as pressure sensors, gas sensors and PDs, could also be used in industry, bio‐organs, and under harsh environments 167, 168, 169, 170.…”
Section: New Concepts In Flexible Pd Design With 1d Inorganic Nanostrmentioning
confidence: 99%